TRANSLATION TECHNIQUES IN ALANI HAPOGOSON MOVIE - Monica, Hana; Sinaga, Lidiman Sahat Martua; Hasibuan, Juli Rachmadhani (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study deals with translation technique in Alani Hapogoson movie. The aims of the study are to analyze the techniques used in translating the movie, to find the most dominant one used in translating the movie and describe the most dominant one in translating the movie. It uses the six theory of Molina and Albir, which are adaptation, calque, compensation, linguistic amplification, linguistic compression and literal translation. In analyzing the data, the research was conducted by using descriptive qualitative method. The data were taken from Sahat™s utterances in œAlani Hapogoson movie which consist of Batak Toba and Bahasa. In Sahat™s Utterances of Alani Hapogoson movie the result of literal translation 117 sentences (96%) belongs to dominant technique that applied in the movie, followed by calque 3 sentences (2,46%) and compensation 2 sentences (1,64%) takes from six techniques. There are three process in translating the dominant technique 1) analysis, 2) transfer and 3) restructuring.